Gut Dysfunction Markers Are Associated With Body Composition in Youth Living With Perinatally Acquired Human Immunodeficiency Virus . (28th January 2022) - Dirajlal-Fargo, Sahera; Jacobson, Denise L; Yu, Wendy; Mirza, Ayesha; Geffner, Mitchell E; Jao, Jennifer; McComsey, Grace A
Abstract: Background: The association between gut dysfunction and body fat composition in youth living with perinatal human immunodeficiency virus infection (YPHIV) has not been investigated. Methods: We included YPHIV aged 7–19 years from the Pediatric HIV/AIDS Cohort Study Adolescent Master Protocol with plasma available within 6 months of baseline whole-body dual energy x-ray absorptiometry (DXA) and HIV RNA ≤1000 copies/mL within 3 months of baseline DXA and a second DXA 2 years later. Plasma markers of bacterial translocation and gut barrier dysfunction (lipopolysaccharide binding protein [LBP], zonulin, and intestinal fatty acid binding protein [I-FABP]) were measured at baseline by enzyme-linked immunosorbent assay and log10 transformed. Adiposity outcomes included percentage total body, truncal, and extremity fat in kilograms from DXA. Linear regression models were fit using generalized estimating equations to assess associations of baseline gut markers (log10 ) on adiposity outcomes at baseline and 2 years, adjusted for demographic variables, current antiretroviral therapy exposure, and physical activity. Results: Two hundred sixty-one youth were included; 128 had a second DXA. Median age at first DXA was 12 years (interquartile range, 10–14 years), 49% were female, and 69% were Black. After adjustment for potential confounders, log10 LBP was positively associated with percentage total body fat at baseline (β = 4.08, P  < .01) and zonulin with adiposity measures at both time points (β = .94 to 6.50, P  ≤ .01). I-FABP was inversely associated with percentage total body fat at baseline and year 2 (β = –2.36 and –3.01, respectively, P  ≤ .02). Conclusions: Despite viral suppression, gut damage and the resultant bacterial translocation are associated with body composition measures in YPHIV. Abstract : Abnormal gut barrier dysfunction is associated with adiposity in youth with perinatally acquired HIV despite viral suppression with antiretroviral therapy.